MicroRNA-155 suppresses autophagy in chondrocytes by modulating expression of autophagy proteins. Issue 6 (June 2016) - D'Adamo, S.; Alvarez-Garcia, O.; Muramatsu, Y.; Flamigni, F.; Lotz, M.K.
Summary: Objective: Autophagy dysfunction has been reported in osteoarthritis (OA) cartilage. The objective of this study was to investigate the role of microRNA-155 (miR-155), which is overexpressed in OA, in the regulation of autophagy in human chondrocytes. Design: Rapamycin (50 nM) and 2-deoxyglucose (2-DG) (5 mM) were used to stimulate autophagy in primary human articular chondrocytes and in the T/C28a2 human chondrocyte cell line. Cells were transfected with LNA GapmeR or mimic specific for miR-155 and autophagy flux was assessed by LC3 western blotting and by Cyto-ID ® dye quantification in autophagic vacuoles. Expression of predicted miR-155 targets in the autophagy pathway were analyzed by real-time PCR and western blotting. Results: Autophagy flux induced by rapamycin and 2-DG was significantly increased by miR-155 LNA, and significantly decreased after miR-155 mimic transfection in T/C28a2 cells and in human primary chondrocytes. These effects of miR-155 on autophagy were related to suppression of gene and protein expression of key autophagy regulators including Ulk1, FoxO3, Atg14, Atg5, Atg3, Gabarapl1, and Map1lc3. Conclusion: MiR-155 is an inhibitor of autophagy in chondrocytes and contributes to the autophagy defects in OA.